Одержання акрилової кислоти альдольною конденсацією оцтової кислоти з формальдегідом на V-Ti-PO₄ каталізаторах - Шпирка, Ірина Іванівна; Небесний, Роман Володимирович; Піх, Зорян Григорович; Сидорчук, Володимир Васильович; Івасів, Володимир Васильович; Халамейда, Світлана В'ячеславівна; Завалій, Катерина Вадимівна (НТУ "ХПІ", 2017)
Досліджено закономірності процесу альдольної конденсації оцтової кислоти з формальдегідом в акрилову кислоту у газовій фазі на V-Ti-PO₄ каталізаторах. Встановлено вплив температури процесу на конверсію реагентів та селективність утворення продуктів реакції. Встановлено вплив умов приготування каталізаторів, а саме методу одержання активної фази каталізатора та прожарювання каталізатора на його ефективність у досліджуваному процесі. Запропоновано оптимальну методику приготування V-Ti-PO₄ каталізатора та оптимальні умови одержання акрилової кислоти.

The purpose of this work is to research process of aldol condensation of acetic acid with formaldehyde to acrylic acid in the gas phase, namely: to develop effective catalysts for the process of aldol condensation with acetic acid to acrylic acid; to determine optimum conditions for the process; to investigation of the influence of titanium content in a V-Ti-PO₄ catalyst and the effect of catalyst calcination on its efficiency in the process of aldol condensation of acetic acid with formaldehyde to form acrylic acid. In order to solve this problem, we designed catalysts based V-Ti-PO₄ catalysts. The effect of temperature was examined on the conversion of reagents, the selectivity of formation and the yield of acrylic acid on the created catalysts. With increasing temperature, the conversion increases, the selectivity of formation of acrylates decreases and the total yield of acrylic acid has the maximum. It was shown that the effect of calcination of the catalysts doesn’t significantly affect their efficiency in investigated process. It was determined that after calcining the activity of the catalyst K1 has decreased. The yield of acrylic acid on the non-roasted catalyst is 40%, and on the roasted catalyst - 19%. At the catalyst K2, the acrylic acid slightly increased - 18.2%, but the selectivity acrylic acid of decreased. Application of the developed catalyst, synthesized by co-precipitation of TiOSO₄ and VSO₄ from aqueous solution, allows to achieve 29 % yield of acrylic acid, 30 % acrylic acid selectivity at 97 % acetic acid conversion. The optimum conditions for acrylic acid obtaining are 648 K and 8 s residence time.
Acrylic acid synthesis by aldol condensation of acetic acid and formaldehyde on V-Ti-PO₄ catalysts
Keywords: гетерогенний каталіз; конверсія; температура; газова фаза; реагент; продукти реакції; heterogeneous catalysis